Bibliometric Analysis on Sustainable Finance and Technological Innovation for Climate Change Mitigation - Judijanto, Loso (Westscience Press, 2025)
The growing urgency of climate change has intensified scholarly interest in sustainable finance and technological innovation as key mechanisms for climate change mitigation. While research in this area has expanded rapidly across disciplines, the literature remains fragmented, making it difficult to identify dominant themes, influential contributors, and emerging research directions. This study aims to provide a comprehensive bibliometric analysis of global research on sustainable finance and technological innovation for climate change mitigation. Using data retrieved from the Scopus database, this study applies bibliometric techniques to examine publication patterns, citation structures, co-authorship networks, institutional and country collaborations, and keyword co-occurrence relationships. Visualization and mapping analyses were conducted using VOSviewer to reveal the intellectual structure and temporal evolution of the field. The results show that climate change and sustainable development constitute the core research themes, closely linked with green finance, renewable energy, circular economy, and climate policy. Recent trends indicate a growing emphasis on technology-driven approaches, particularly the integration of artificial intelligence and innovation-oriented financial mechanisms. However, research related to developing countries and inclusive climate finance remains relatively underexplored. This study contributes by offering a systematic overview of the knowledge landscape, identifying research gaps, and highlighting future directions for advancing climate change mitigation through sustainable finance and technological innovation.